Selection of high-yielding, adapted and stable wheat lines in preliminary trials - Woyann,Leomar Guilherme (2019)
Abstract Experimental design without replication, such as Federer's augmented block design, allows us to determine productivity, adaptability and stability in multi-environment trials. This work aimed to select productive wheat lines with high adaptability and stability in preliminary trials. The grain yield of 140 homozygous wheat lines was measured in 2015 at three locations. The cultivar TBIO Mestre was used as a check. Genetic parameters were evaluated by mixed models, and selection was based on the harmonic mean of the relative performance of the genetic values (HMRPGV) using models 74 (individual analysis) and 75 (joint analysis) of Selegen software. In the joint analysis, 33 wheat lines stood out in terms of productivity, adaptability and stability. These lines have the potential to be evaluated in Value for Cultivation and Use (VCU) trials for future release of new wheat cultivars.